2021
DOI: 10.3390/ijerph18158124
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Care and Unmet Needs in Upper Gastrointestinal Cancer Patients: Screening and Related Factors

Abstract: Upper gastrointestinal (UGI) cancer treatment can cause physical and psychological distress and may result in unmet needs. The purposes of this study were to (1) examine the levels of gastrointestinal (GI) symptom distress, social support, and supportive care needs; (2) screen the priorities of unmet supportive care needs; and (3) identify the factors associated with supportive care needs among UGI cancer patients receiving chemotherapy. This cross-sectional study examined UGI cancer patients who received trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(56 reference statements)
1
3
1
Order By: Relevance
“…Previous research conducted among Chinese cancer patients has shown that unmet needs at the end of treatment were the lowest, and psychological needs were more prevalent 35 . This is in line with previous research showing that cancer patients did not receive sufficient psychological support in China 35,36 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous research conducted among Chinese cancer patients has shown that unmet needs at the end of treatment were the lowest, and psychological needs were more prevalent 35 . This is in line with previous research showing that cancer patients did not receive sufficient psychological support in China 35,36 …”
Section: Discussionsupporting
confidence: 84%
“…35 This is in line with previous research showing that cancer patients did not receive sufficient psychological support in China. 35,36 This study is the first to demonstrate that self-compassion can be a protective factor for unmet needs and can predict their development in cancer patients. Future studies should explore more positive factors related to unmet needs, so as to contribute to reducing the level of unmet needs and improving the patients' quality of life.…”
Section: Discussionmentioning
confidence: 91%
“…This study identified the relationship between disease complexity, quality of life, and supportive care needs in female patients with genital cancer in South Korea and clarified the effects of these variables on the patients' supportive care needs. The level of supportive care needs was found to be 47.44 of 100 points, which is higher than the 34.25 points calculated in a study on patients with gastric cancer in South Korea [34] using an abbreviated version of the tool used in this study. Direct comparison is difficult since there is no earlier study that examined the same disease.…”
Section: Discussioncontrasting
confidence: 82%
“…Importantly, high distress at the time of starting chemoradiotherapy reflected a higher number of unmet needs, demonstrating the strong relationship between distress and unmet needs as seen in other populations during active treatment 32,33 through to survivorship. 34,35 Regular monitoring of patient distress is necessary as distress was prevalent at all three time points.…”
Section: Discussionmentioning
confidence: 85%